The European Banking Union: Will It Be a True Union without Risk Sharing? - Sarcinelli, Mario (PSL Quarterly Review, 2013)
The recent developments of the Euro crisis reveal the lack of clear or coherent thinking on the part of both the Eurozone finance ministers and the European Commission. The crisis in Cyprus is partly the consequence of decisions made on private sector involvement in the previous Greek bailout, and other such examples may be made. It is time, therefore, to look reality in the face and strengthen the structures of the EMU. The article is devoted to what has been done and what must still be done to make the European banking system more robust and less permeable to crises, and to preserve the single financial market. It looks at the initiatives of both the European Commission and the European Council to complete the EMU by creating a banking union, the doubts on the wisdom of entrusting banking oversight to the ECB, the organization of the ECB’s new tasks, the continuing absence of facilities for the recovery or liquidation of banks, as well as for a Euro-wide deposit insurance, the need for some form of risk-sharing in order to stabilise the economy, and thus the recourse to a common budget and the possibility of joint debt for the Eurozone. JEL Codes: G01, G28, G18